Systemic interaction between educators of choreographic disciplines under distance learning conditions - Yatsenko, Olha; Khomiachyk, Ilona; Hladka, Liudmyla; Vasina, Nadiia; Koresandovych, Natalia; Slupska, Nataliia (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Distance learning is an essential component of modern choreographic education under quarantine restrictions. It puts new tasks in front of the academic teaching staff, administrators, managers, and other educational process participants; it demands new rules of interaction. The aim of this study was to identify the main problems and difficulties encountered in choreographic education under distance learning conditions, as well as to present a set of teaching activities intended to alleviate rejection and anxiety about the changes in teaching by all educational process participants. The article highlights several activities to find ways to enhance interaction between teachers and accompanists. We used a comprehensive approach to methodology: descriptive method, analysis, and synthesis to consider the theoretical foundations, statistical methods (qualitative and quantitative), the method of questioning, as well as the method of a pedagogical experiment - collection, description and analysis of the practical results of behavioral research. Choreographic education needs close interaction between all participants in the educational process under distance learning conditions. The latter relieves stress and improves the attitude to the work of the choreographer within the conditions changed due to quarantine restrictions. This interaction is facilitated by using the possibilities of digital space and the virtualization of the educational process. Further research should consider successful forms and methods of teaching choreography under distance learning conditions and look for effective ways of improving the interaction between all participants in the educational process.